ANALISIS KESALAHAN PESERTA DIDIK KELAS VIII DALAM MENYELESAIKAN SOAL MATERI PERSAMAAN GARIS LURUS - Abdul Hakim; Ibrahim Aji (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2022)
This study aims to examine the difficulties faced by students in solving problems on the material of straight line equations for class VIII. This research is a type of descriptive research using a qualitative approach. The subjects of this research are the class VIII students of SMP Negeri 2 Ciranjang as many as 22 students. From this study, it can also be concluded that students lack mastery of the concept of straight line equations and lack of student interest in learning to learn more about mathematics.